Does involvement in one outdoor activity reduce participation in other activities: Are enthusiastic fishers only fishers?. (March 2018) - Sievänen, Tuija; Neuvonen, Marjo; Pouta, Eija
Abstract: This study examined involvement in outdoor recreation activities, focusing on whether individuals who are involved in one recreation activity at a high level are less or more likely to participate intensively in other outdoor activities. Participation in fishing in Finland was taken as a starting point. The data were obtained from a large national population survey that included 3592 respondents who participated in fishing. Three groups were distinguished based on behavioral involvement in fishing. The high behavioral involvement (HBI) group reported the highest annual frequencies for most outdoor activities. The moderate behavioral involvement (MBI) group were modestly active in fishing, and moderately active in outdoor recreation in general. Compared to the other groups, the low behavioral involvement (LBI) group participated least frequently in fishing and were also less active in many other recreational activities. The results imply that behavioral involvement in outdoor recreation is cumulative in nature. Management implications: The study provides interesting findings for rural tourism and land use management: ● A high level involvement in one activity is not necessarily reducing the participation intensity in others. ● In order to understand activity clusters and key activities in a region, it is strongly recommended to investigate the whole palette of outdoor recreation activities. ● Within the group of fishermen various subgroups exist, which are characterized by different motivation and behavioral patterns. ● These insights may help in offering substitutes for fishing activities or new service packages that include a broader array of activities for people to participate, and to extend their stay and enhance their contribution to the regional economy.